Case Report: Long-Term Response to Pembrolizumab Combined With Endocrine Therapy in Metastatic Breast Cancer Patients With Hormone Receptor Expression - Wu, Dingyong; Tang, Shu; Ye, Rong; Li, Dongmei; Gu, Dejian; Chen, Rongrong; Zhang, Huan; Sun, Jianguo; Chen, Zhengtang (Frontiers in Immunology, 2021)
Breast cancer is one of the most frequently diagnosed malignancies. Although endocrine therapy improved the survival of hormone receptor (HR) positive patients, the post-endocrine therapy strategy to metastatic breast cancer remained a great challenge. In this study, we reported two cases that benefited from antiestrogen combined with immunotherapy regimen to support that the immunotherapy combination strategy may be a potential treatment to post-endocrine patients with HR positive metastatic breast cancer. Case 1 was a relapsed breast cancer patient with ovarian and brain metastasis after endocrinotherapy. After surgery for ovarian, she received three cycles of chemotherapy. Given that the lesions on the brain did not change and higher T cell receptor (TCR) repertoires (higher Shannon index and Clonality) of tumor, she adopted letrozole combined with pembrolizumab treatment. Then, the patient achieved partial response, and the progression free survival (PFS) lasted over 21 months. Case 2 was a breast cancer patient with multiple bone metastases. After failure of combined radiotherapy and chemotherapy, the patient received tamoxifen combined with pembrolizumab based on the higher TCR repertoires (higher Shannon index and Clonality) of tumor. The patient's bone pain and biomarker were relieved after treatment. The patients completed 6 cycles of pembrolizumab and PFS has lasted over 21 months. In conclusion, our study confirmed that antiestrogen combined with immunotherapy regimen was a promising treatment to patients with higher TCR repertoires and HR positive metastatic breast cancer.